Les giletes de Francesc Fontanella com a model d'una literatura catalana culta. - CASTAÑO TRIAS, MARTA (Scripta, 2017)
Francesc Fontanella wrote 77 love poems dedicated to Gileta. The group of poems called giletes (because of the name of the pseudonym of the lady) became one of the most copied parts of his literary production in manuscripts and in printed materials; in some of the unitarian manuscripts they even have their own cover. The imitations of the anonymous authors who are specifically inspired by the work of Fontanella also prove the cultural impact of the poems to Gileta. These imitations have been copied in several manuscripts and they represent, from different points of view, the legacy of the Barcelonan baroque poet in the Catalan literature.